Produksi Kompos dari Bungkil Biji Malapari (Pongamia pinnata L.) - Taebenu, Desi Adriyanti Nina; Arpiwi, Ni Luh; Astarini, Ida Ayu (BIOEDUSCIENCE, 2025)
Background: Biodiesel production from malapari seeds generates waste in the form of seed cake that can still be utilized. This seed cake can be processed into compost because it contains various essential minerals for plant growth. This study analyzes the quality of compost made from malapari seed cake based on the SNI 19-7030-2004 standard. Methods: The compost fertilizer was fermented for 31 days using four treatments. (P1) malapari cake 1kg + Orgadec 2g; (P2) malapari cake 334g + goat manure 333g + burnt rice husk 333g + Orgadec 2g; (P3) Malapari cake 200g + goat manure 400g + burnt rice husk 400g + Orgadec 2g; (P4) Malapari cake 400g + goat manure 200g + burnt rice husk 200g + Orgadec 2g. Results: Water, phosphorus, and potassium content tests in treatments P1, P2, P3, P4 met specifications. pH tests in treatments P1, P2, P4 met specifications, P3 did not meet specifications. Nitrogen tests in P1 and P2 met specifications, but P3 and P4 did not. The organic C test in P1 did not meet specifications, while P2, P3, and P4 met specifications. The electrical conductivity test in P1 met specifications, while P2, P3, and P4 did not. Color and odor in P1 did not meet specifications, while P2, P3, and P4 met specifications. Conclusions: Compost from malapari seed cake has met the compost quality specifications according to SNI 19-7030-2004 for P2, so it is suitable for plant application.